LEGAL ANALYSIS OF ENVIRONMENTAL EDUCATION IN ACCORDANCE WITH INDONESIAN LEGISLATION - Ventyrina, Ine; Syahrin, Alvi; Sitepu, Runtung; Ginting, Budiman; Suhaidi, Suhaidi; Leviza, Jelly (Faculty of Law Universitas Panca Bhakti, 2019)
Increased awareness of environmental issues is leading to the introduction of environmental education. This article discusses some of Indonesian legislations that accompany the introduction and development of environmental education. Research results concluded that environmental education has been mandatory in various Indonesian legislations which has? been observed with vertical and horizontal synchronization, in accordance with the purpose and scope of the environmental protection and management in article 3 and article 4 of Act Number 32 the year 2009.